ANALYSIS OF ONLINE ADVERTISING AND PRODUCT DISCOUNTS ON SALES VOLUME OF BREASTFEEDING CLOTHES PRODUCTS IN ONLINE STORES - Arvi, Reza Nur; Pamuji, Geraldi Catur (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The aim of this research is to see the effect of online advertising and product discounts on the sales volume of breastfeeding clothing products in online stores via the Shopee application. The research uses quantitative method where observation was done through a total of 45 companies registered in the Shopee as a sample of data with a sales period of breastfeeding clothes from 2015 to 2022. The collected data was then plotted through a graph and analyzed to see the correlation using statistical method. The results of the research show that although the number of companies selling breastfeeding clothes continues to increase every year (X), sales of breastfeeding clothes also continue to increase every year (Y), this shows that the influence of online advertising and product discounts has a positive impact on the sales volume of breastfeeding clothing products